Finding My Place: Birth Mothers Manage the Boundary Ambiguity of Adoption Reunion Contact - March, Karen (Qualitative Sociology Review, 2015)
This study describes how essentialist notions of motherhood infl uence adoption reunion outcomes. The data analysis is based primarily on in-depth interviews with 33 reunited birth mothers. Collectively, the birth mothers perceived themselves to be the mothers of a child lost to them through adoption. Reunion contact jeopardized this perception when the mothers met adopted adults who did not accept their mothering overtures. Continued contact meant suppressing their motherhood desires and taking on a reunion role more consistent with their adoption triad position.